Tinjauan tentang Fasilitas Homestay Di Kawasan Saribu Rumah Gadang Kabupaten Solok - Tuti Utari; Waryono (Jurnal Kajian Pariwisata Dan Perhotelan, 2024)
Tourism is an activity that stimulates the economy by creating jobs, where homestays act as accommodation that offers local experiences. The Saribu Rumah Gadang area in South Solok, West Sumatra, is a leading cultural tourism destination which is famous for its traditional Minang Kabau houses. Even though its popularity is increasing, challenges such as narrow road access, lack of standard facilities in homestays, and the lack of supporting facilities such as information boards, are obstacles that must be overcome to increase tourist attraction and comfort. This research uses a qualitative descriptive method, where data is collected naturally without comparing or looking for relationships between variables. The research was carried out at the Saribu Rumah Gadang Homestay Area, South Solok, West Sumatra, in July-August 2024. Informants were selected using snowball sampling techniques, involving the Tourism Office, managers and homestay owners. This research reveals that the facilities at the Saribu Rumah Gadang Homestay area have several advantages and disadvantages. Access to homestays is generally adequate, although some homestays have narrow access and lack of signage. The majority of homestays have good air ventilation, but lighting varies. Bedrooms in homestays are equipped with clean bedding, although not all homestays provide wardrobes, room keys or dressing table facilities. The bathroom is generally attached to the homestay and has sufficient facilities, although some facilities such as towel rails and closed trash cans are still lacking. The kitchen and dining room in the homestay are generally clean and well maintained, while the living room is equipped with adequate tables and chairs. However, the availability of supporting facilities such as signage is still limited, because homestay owners consider it not very important.